Alkyl chain length dependent morphology and emission properties of the organic micromaterials based on fluorinated quinacridone derivatives - Zhao, Yunfeng (Langmuir : the ACS journal of surfaces and colloids, 2009)
The fluorinated quinacridone derivatives N,N'-dialkyl-2,9-difluoroquinacridone (Cn-DFQA, n = 4, 8, 10, 16) with different alkyl chains were used as building blocks to assemble luminescent micromaterials. It was demonstrated that the morphology and emission of the Cn-DFQA-based micromaterials strongly depended on their alkyl chain length. C4-DFQA and C8-DFQA showed stronger tendency to form 1-D microstructures, while C10-DFQA and C16-DFQA displayed the aggregation properties to form diamond and hexagonal platelike microcrystals, respectively. The photoluminescent (PL) spectra of Cn-DFQA (n = 4, 8, 10, 16) in THF dilute solutions displayed approximate profiles with a sharp emission peak at 533 nm and a shoulder at 573 nm, while the PL spectra of the Cn-DFQA-based micromaterials exhibited obviously red-shift emission bands at 622 nm for C4-DFQA, 627 nm for C8-DFQA, 614 nm for C10-DFQA, and 613 nm for C16-DFQA, respectively. The single-crystal X-ray structures of four Cn-DFQA compounds have been studied. In the C4-DFQA and C8-DFQA single crystals, there are 1-D molecular columns based on the intermolecular pi...pi and hydrogen bonding interactions. In the single crystals of C10-DFQA and C16-DFQA, the molecules assembled into 2-D molecular sheets based on the hydrogen bonds and C-H...pi interactions. The molecular packing structures provide a reasonable explanation for the alkyl chain length dependent morphologies and emission properties of fluorinated quinacridone micromaterials